What Determines Metropolitan Jakarta’s Muslim Intention to Use M-Banking? - Muhammad Khaerul Muttaqien; Moh Khoirul Anam; Tajudin Mas'ud Tajudin; Hamli Syaifullah Hamli (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study was to determine the factors that influence the usefulness, trustworthiness, and acceptance of M-Banking. The theoretical framework used in this study is the Technology Acceptance Model (TAM), with the addition of perceived risk and trust variables. Research data collected from 265 Muslims in the Jakarta Metropolitan area were analysed using a statistical method known as Partial Least Squares Path Modeling. These findings indicate that the intention to use M-Banking is positively and significantly influenced by trustworthiness, easiness, and perceived risk. Meanwhile, the intention to use M-Banking is not affected based on the perceived usefulness. According to the findings, perceived usefulness and easiness have a positive and significant effect on trust. Furthermore, perceived risk and easiness have a positive and significant effect on perceived usefulness. Practical implications by considering the antecedents of usefulness, trust and acceptance of M-Banking, the banking industry can improve the service quality and security of M-Banking.